Perancangan Ulang Sekolah Dasar Salman Al-farisi Menggunakan Pendekatan Fleksibilitas - Griselda Putri, Zara; Firmansyah, Rangga; Sri Ismiranti, Athifa (eProceedings of Art & Design, 2024)
Primary education serves as the foundational stage for children's social and cognitive development, which will impact their future. In the modern era, many elementary schools are implementing a fullday school system, applying the concept of flexibility to both curriculum and physical space. This aims to optimize the learning process by adjusting teaching methods and classroom arrangements to meet students' needs and learning styles. This study will explore the use of flexible furniture to create an adaptive and inclusive learning environment. Keywords: education, flexibility, furniture, adaptive